If f(x)=5x-2 and g(x)= cubed sqrt of x ( or x^(1/3)), evaluate (fog)(-8)
- print Print
- list Cite
Expert Answers
hala718
| Certified Educator
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
Given that:
f(x) = 5x-2.
g(x) = (x^1/30
We need to find fog(x)
First we will rewrite fog(x) as follows:
fog(x) = f(g(x))
We will substitute with g(x) = x^1/3
==> fog(x) = f(x^1/3)
Now we will substitute with x^1/3 in f(x)
==> fog(x) = 5(x^1/3) -2
Now we will substitute with x=-8.
==> fog(x) = 5(-8^1/3) -2 = 5*-2 -2 = -10 -2 = -12
==> fog(-8) = -12.
check Approved by eNotes Editorial
Related Questions
- Given f(x) and g(x), please find (fog)(X) and (gof)(x) f(x) = 2x g(x) = x+3
- 1 Educator Answer
- If f(x) = x^2+3 g(x) =sqrt(x) determine (fog)(x) and (gof)(x).
- 1 Educator Answer
- If f(x) = 2x-3 and g(x) = x+1 find fog(3) and gof(-2)?
- 1 Educator Answer
- if f(x)=2x-3 and fg(x)=2x+1,find g(x)
- 1 Educator Answer
- If f(x) = 2x-3 and g(x) = x^2 -2 find fog(x) and gof(x).
- 2 Educator Answers
justaguide
| Certified Educator
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
We have f(x) = 5x - 2 and g(x) = x^(1/3) [ I have assumed by cubed sqrt you mean raised to the power (1/3)]
We have to find fog( - 8)
fog(x) = f(g(x)) = f( x^(1/3))
=5 * x^(1/3) - 2
For x = -8
fog(-8) = 5*(-8)^(1/3) - 2
=> 5* (-2) - 2
=> -10 - 2
=> -12
The required result is -12
check Approved by eNotes Editorial
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.